International spillovers and water quality in rivers: Do countries free ride? - Hilary Sigman (Rutgers University, Department of Economics, 2001)
Transboundary spillovers may degrade environmental quality if countries free ride. This paper examines the extent of such degradation in water quality in international rivers. Using data from river monitoring stations in the UN's Global Environmental Monitoring System (GEMS), it compares pollution levels in international and domestic rivers. The results suggest that free riding may substantially increase pollution in international rivers, but the estimates are sensitive to the inclusion of country effects.
Keywords: F00; Q28; 330; Environment; Externalities; Pollution; Grenzüberschreitende Umweltbelastung; Gewässerbelastung; Trittbrettfahrerverhalten; Welt